The Occupational Health Effects of Responding to a Natural Gas Pipeline Explosion Among Emergency First Responders – Lincoln County, Kentucky, 2019. (21st October 2022) - Bui, David P.; Kukielka, Esther A.; Blau, Erin F.; Tompkins, Lindsay K.; Bing, K. Leann; Edge, Charles; Hardin, Rebecca; Miller, Diane; House, James; Boehmer, Tegan; Winquist, Andrea; Orr, Maureen; et al.
Abstract: Objective: The aim of the study was to assess occupational health effects 1 month after responding to a natural gas pipeline explosion. Methods: First responders to a pipeline explosion in Kentucky were interviewed about pre- and post-response health symptoms, post-response health care, and physical exertion and personal protective equipment (PPE) use during the response. Logistic regression was used to examine associations between several risk factors and development of post-response symptoms. Results: Among 173 first responders involved, 105 (firefighters [58%], emergency medical services [19%], law enforcement [10%], and others [12%]) were interviewed. Half (53%) reported at least 1 new or worsening symptom, including upper respiratory symptoms (39%), headache (18%), eye irritation (17%), and lower respiratory symptoms (16%). The majority (79%) of symptomatic responders did not seek post-response care. Compared with light-exertion responders, hard-exertion responders (48%) had significantly greater odds of upper respiratory symptoms (aOR: 2.99, 95% CI: 1.25–7.50). Forty-four percent of responders and 77% of non-firefighter responders reported not using any PPE. Conclusions: Upper respiratory symptoms were common among first responders of a natural gas pipeline explosion and associated with hard-exertion activity. Emergency managers should ensure responders are trained in, equipped with, and properly use PPE during these incidents and encourage responders to seek post-response health care when needed.